A33 MEALTIME SUPPORT: A PILOT COHORT STUDY OF AN EFFECTIVE, COST-SAVING OUTPATIENT HUNGER-BASED FEEDING PROGRAM FOR TUBE DEPENDENCY. (4th March 2021) - Huynh, G; Vishram, A; Graham-Parker, C; Blatz, D; Carroll, M W; Turner, J
Abstract: Background: Tube dependency is an under recognized complication of long-term enteral feeding in young children. Many children struggle to progress to full oral feeds even with sufficient oral motor skills and swallowing ability. Tube dependency greatly impacts the quality of life of children and families and is a significant burden to the health care system. Economic challenges, increased burden of care and psychosocial issues all reinforce the need for timely tube removal. Aims: We aimed to examine the efficacy of a multidisciplinary child-led, hunger-based approach called "Mealtime Support" at the Stollery Children's Hospital in Edmonton. Nutritional outcomes, parental satisfaction and cost implications were evaluated. As a secondary aim we sought to determine the rates of gastrostomy tube insertions in the pediatric age range across Canada as a potential indicator of increasing need for long term tube feeding, hence the need for cost effective tube weaning programs to be developed in Canada. Methods: The ambulatory program was delivered 2–3 times a day, for 2 weeks, by an occupational therapist and dietitian, under medical supervision. Hunger was promoted by reducing tube fed calories by 80% prior to commencement. Top-up tube feeds were given immediately after feeding sessions if needed. Caregivers completed 12-question subjective surveys pre and post intervention. Micro-costing methods compared costs between the program and ongoing tube feeding. The number of pediatric hospital admissions and gastrostomy tube insertions from 2008–2019, per province, was collected from the Canadian Institute for Health Information (CIHI). Results: From 2016 - 2017, 6 children who had been tube fed from 7 to 21 months in total were enrolled and 5 completed the program. At 1-month post intervention, 4/5 of the children were 100% orally fed. Parents reported improvement in mealtime struggles (p-value = 0.005), reduction in worry about their child's eating (p-value = 0.005) and improvement in their child's appetite/variety foods eaten (p-value = 0.004). Over a year the potential cost savings were estimated at $42, 471.24. By 6-months, all feeding tubes were removed. Based on the CIHI data, the number of gastrostomy tubes inserted per 100, 000 children varied significantly between provinces, but highest in Nova Scotia, Saskatchewan and Alberta with increases seen from 2008–2018. Conclusions: The transition from tube feeding to oral feeding is difficult for children who are tube dependent and poses several economic and psychosocial challenges. Mealtime Support was safe and successful in reducing tube dependency and cost-effective compared to no intervention or hospital based programs. There is a need to develop and fund Canadian outpatient feeding programs. Funding Agencies: The Stollery Children's Foundation